Intellectual Capital, Corporate Sustainability Report, and Firm Size On Company Values: Emperical Study Of Property Company - Muhammad Wildan Affan; Dehanna Puspitasari (Universitas Muhammadiyah Malang, 2023)
Purpose: This research aimed to analyze the effect of intellectual capital, CSR and firm size on firm value Methodology/Approach: this research used a purposive sampling technique and data analysis used multiple linear regression. Data collection uses documentation techniques in the form of data through the Indonesian Stock Exchange publication website. Findings: The results that indicate intellectual capital has an effect on firm value; CSR has no effect on firm value and firm size has a significant effect on firm value. Practical and Theoretical Contribution/Originality: Property sector companies should maintain company performance to remain stable, namely by maximizing intellectual capital and company size, so as to maintain the stability of company value. Research Limitation: The research method used cannot provide a detailed explanation for research results that are not in line with the existing theory, namely the relationship between CSR and company value.